Online home finder system / Tang Ping Ping - Tang, Ping Ping (2004)
The aim of proposed project is to develop a web-based system called Online Home Finder System. Day by day the burden of house for sale or rent advertisement under classified section in newspaper keeps on increasing and is quite hard and also quite wasting time for house seekers to find their house. In this new era, internet grow rapidly and becoming an attractive advertising media for various sectors. HousingLane.com.my is among the successful online advertising locally from those four existing systems that I studied and analyzed. Quite similar to HousingLane.com.my concept in the sense to allow advertiser to place advertisement at website and the website would provide searchable database for targeted viewers. This project draft which covered specifications for developing OHFS. Chapter I present introduction defmes project overview, objectives, scope limitations, expected come project and the targeted users. The next chapter, Chapter 2 is discuss about the finding of literature review has been carried out earlier which include judgments and opinions on existing system that being studied and analyzed. Discuss various supporting tools and technologies that related to develop project also done in this chapter. Chapter 3 is focusing in the discussion about the methodology will be implemented in system development process. It also discusses the reasons of selecting proposed methodology to a next deeper step. For Chapter 4, it discuss about the various requirements analysis have been carried out in. Functional and non-functional requirements are completely documented in this chapter. It also included the summary of tools and technologies chosen to develop system. Chapter 5 are presents system design using various techniques such as context diagram, data flow diagram and flow diagram. It also include with database design and user interface design.